Am i not (yet or already) old enough? (In)visibility, vulnerability and violence of children and elderly - Bernardini, Maria Giulia (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
In the legal reflection, the issue of violence has a crucial relevance. In particular, critical literature has focused on the structural character of this phenomenon with respect to certain subjects and groups, indicated as “vulnerable”, stressing how, in addition to the legal field, the issue concerns also to the sociocultural one. Indeed, violence receives in the socio-cultural dimension its first legitimation. Assuming this theoretical-conceptual framework as a basis, the Author reflects on the nexus among (in)visibility, vulnerability and violence with respect to minors and the elderly; that is, in relation to “age”.
Keywords: age; ageism; invisibility; vulnerability; violence